Prenatal Management of Pregnancies at Risk of Fetal Neonatal Alloimmune Thrombocytopenia (FNAIT): Scientific Impact Paper No. 61. (9th April 2019) - Regan, F; Lees, CC; Jones, B; Nicolaides, KH; Wimalasundera, RC; Mijovic, A; ,
Plain language summary: What is it?: Fetal neonatal alloimmune thrombocytopenia (FNAIT), also known as neonatal alloimmune thrombocytopenia (NAIT) or fetomaternal alloimmune thrombocytopenia (FMAIT), is a rare condition which affects a baby's platelets. This can put them at risk of problems with bleeding, particularly into the brain. One baby per week in the UK may be seriously affected and milder forms can affect one in every 1000 births. How is it caused?: Platelets are blood cells that are very important in helping blood to clot. All platelets have natural proteins on their surface called human platelet antigens (HPAs). In babies, half of these antigens are inherited from the mother and half from the father. During pregnancy, some of the baby's platelets can cross into the mother's bloodstream. In most cases, this does not cause a problem. But in cases of FNAIT, the mother's immune system does not recognise the baby's HPAs that were inherited from the father and develops antibodies, which can cross the placenta and attack the baby's platelets. These antibodies are called anti‐HPAs, and the commonest antibody implicated is anti‐HPA‐1a, but there are other rarer antibody types. If this happens, the baby's platelets may be destroyed causing their platelet count to fall dangerously low. If the platelet count is very low there is a risk to the baby of bleeding into their brain before they are born. This is very rare but if it happens it can have serious effects on the baby's health. How is it inherited?: A baby inherits half of their HPAs from its mother and half from its father. Consequently, a baby may have different HPAs from its mother. As the condition is very rare, and even if the baby is at risk of the condition we have no way of knowing how severely they will be affected, routine screening is not currently recommended. What can be done?: FNAIT is usually diagnosed if a previous baby has had a low platelet count. The parents are offered blood tests and the condition can be confirmed or ruled out. There are many other causes of low platelets in babies, which may also need to be tested for. As the condition is so rare, expertise is limited to specialist centres and normally a haematologist and fetal medicine doctor will perform and interpret the tests together. Fortunately, there is an effective treatment for the vast majority of cases called immunoglobulin, or IVIg. This 'blood product' is given intravenously through a drip every week to women at risk of the condition. It may be started from as early as 16 weeks in the next pregnancy, until birth, which would be offered at around 36–37 weeks. Less common treatments that may be considered depending on individual circumstances include steroid tablets or injections, or giving platelet transfusions to the baby. What does this paper tell you?: This paper considers the latest evidence in relation to treatment options in the management of pregnancies at risk of FNAIT. Specifically, we discuss the role of screening, when IVIg should be started, what dose should be used, and what evidence there is for maternal steroids. We also consider in very rare selected cases, the use of fetal blood sampling and giving platelet transfusions to the baby before birth. Finally, we consider the approaches to blood testing mothers to tell if babies are at risk, which is offered in some countries, and development of new treatments to reduce the risk of FNAIT.